The influence of ownership structure, board of directors, and the audit committee on sustainability report disclosure - Wahidah Purnamasari; Akhmad Samsul Ulum; Titi Rahayu Prasetiani (Universitas Pekalongan, 2024)
This study aims to analyze the influence of ownership structure, the board of directors, and audit committees on the disclosure of sustainability reports in the main sector companies listed on the Indonesia Stock Exchange in 2018–2021. This type of research is called correlational research. The population in this study are the main sector companies listed on the IDX in 2018–2021. The sampling technique used was the purposive sampling method, which obtained as many as 13 companies that match the research criteria. The analysis technique used in this study is a multiple linear regression analysis. The results of the study show that the ownership structure has no effect on sustainability report disclosures. The Board of Directors has no effect on the Sustainability Report Disclosure. The Audit Committee has a positive and significant effect on sustainability report disclosures.